The influence of oculomotor tasks on postural control in dyslexic children - Bucci, Maria Pia; Mélithe, Damien; Ajrezo, Layla; Bui-Quoc, Emmanuel; Gérard, Christophe-Loic (Frontiers in Human Neuroscience, 2014)
Dual task is known to affect postural stabilty in children. We explored the effect of visual tasks on postural control in dyslexic and in age-matched non-dyslexic children. Thirty dyslexic children (mean age: 9.80 ± 0.28 years) were compared with thirty non-dyslexic children (mean age: 9.92 ± 0.35 years). All children underwent ophthalmologic and optometric evaluation. Eye movements were recorded by a video-oculography system (EyeBrain ® T2) and postural sway was recorded simultaneously by a force platform (TechnoConept®). Both groups of children performed fixations, pursuits, pro- and anti-saccades tasks. Dyslexic children showed significantly poor near fusional vergence ranges (convergence and divergence) with respect to the non-dyslexic children. During the postural task, quality of fixation and anti-saccade performance in dyslexic children were significantly worse compared to non-dyslexic children. In contrast, the number of catch-up saccades during pursuits and the latency of pro-and anti-saccades were similar in both groups of children examined. Concerning postural quality, dyslexic children were more unstable than age-matched non-dyslexic children. For both groups of children tested we also observed that executing saccades (pro- and anti-saccades) reduced postural values significantly in comparison with fixation and pursuit tasks. The impairment in convergence and divergence fusional capabilities could be due to an immaturity in cortical structures controlling the vergence system. The poor oculomotor performance reported in dyslexic children suggested a deficit in allocating visual attention and their postural instability observed is in line with the cerebellar impairment previously reported in dyslexic children. Finally, pro- or anti-saccades reduce postural values compared to fixation and pursuit tasks in both groups of children tested, suggesting a different influence of visual tasks on postural control according to their attentional demand.